The audiolingual method and meaningful activities to improve the producive skills - Ochoa Fajardo, Gabriela
The Audiolingual Method created a great revolution in teaching foreign languages several years ago. It had its basis on mechanical learning that comes from behaviorism. The Audiolingualism methodology expected students to be able to communicate in the target language through memorization of grammatical structures and word sounds. As the method, it is not concerned of the person; it uses the same techniques to teach the language: memorization, substitution, and repetition. The teacher is the only one who can provide relevant explanation and experiences during the class time. With the Cognitivism theory, methodologies are no longer a unique truth. Teachers can re-do any methodology to adapt it in benefit of their students. Piaget proposes students to create their own learning, meaningful learning, if teachers join all students` backgrounds with the new information which is presented. Despite of the fact that the Audiolingual Method and behaviorism are different from cognitivism, we will see how they can be joined in some practical activities that may help students improve their productive skills. Speaking and writing a new language is a big barrier students have to overcome if they want to lose their fears of communicating in a foreign language. Teachers are responsible to teach students rules, grammar patterns, vocabulary, word sounds, etc, but if students do not learn how and when to use them, there will not be reason to teach or to learn a foreign language. Teachers have to focus on the objective of making their students use the language in their real lives.